The Oxford companion to politics of the world - Krieger, Joel, 1951- (New York : Oxford University Press, 2001)
Presents 672 alphabetized, cross-referenced articles on concepts, events, people, places, and other topics related to politics around the world. Includes brief overview articles as well as interpretive essays, and paired essays of differing perspectives on critical issues.
Includes bibliographical references and index.
Booklist.
Choice.
Adult
Keywords: Political science -- Encyclopedias; World politics -- Encyclopedias; Political science -- Encyclopedias; World politics -- Encyclopedias